Searching Correlations Between Communication and Motivation - Blaskova, Martina; Blasko, Rudolf; Borkowski, Stanislaw; Rosak-Szyrocka, Joanna (Communications - Scientific letters of the University of Zilina, 2016)
The aim of the paper is to examine various contents of the relations between communications (including informativeness), and motivation, i.e. consider the benefits of effective communication as well the risks of ineffective communication acting on motivation, perceive feedback as sustainable and accelerative element of any communication system, reflect on communication and informativeness as motivational tools, consider the need to motivate employees for quality communication and raising awareness in the organization and so on. The empirical part presents the most significant results of Slovak-Polish research in motivation regarding the linkages of informativeness, communication and motivation. Conclusion of the paper stresses the need to achieve a state in which effective communication will actually lead to permanent harmonizing all the motivations in the organization, i.e. all kinds of motives (individual, group and organizational) will be mutually harmonized.